Kierkegaard's dialectic of inwardness : a structural analysis of the theory of stages - Dunning, Stephen N. (Stephen Northrup), 1941- (Princeton legacy library, 1985)
Stephen Dunning examines Kierkegaard's theory of stages in terms of his dialectic of inwardness, shown here to be the Ariadne's thread" uniting all the major pseudonymous works. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905